New records of Pectinariidae (Polychaeta) from Lizard Island, Great Barrier Reef, Australia and the description of two new species - Wong, Eunice; Hutchings, Pat (Zootaxa, 2015)
Five species of Pectinariidae have previously been reported from Australia. This study documents the first records of this family from the Lizard Island region: Pectinaria antipoda is recorded, in addition to its already currently wide Australian distribution; two new species, Amphictene lizardensis n. sp. and Pectinaria carnosus n. sp. were also discovered and described. A key to all Australian species of Pectinariidae is provided.